Comparative nutrient utilization and growth performance of Bhadawari and Murrah buffalo calves under grazing - DAS, M M; SINGH, SULTAN; MOJUMDAR, A B (The Indian Journal of Animal Sciences, 2010)
Comparative nutrient utilization and growth performance were studied in Bhadawari and Murrah buffalo calves (6 each) under grazing with supplementation of concentrate mixture (1% of body weight) and wheat straw ad libitum at stall from July to September. The pasture crude protein content reduced from 6.82% to 5.88% whereas NDF content increased from 69.54% to 72.27% with advancement of maturity of pasture from July to September. Total DMI was comparable in Bhadawari and Murrah buffaloes. DM intake from pasture was also comparable; however, pasture intake as percentage of total DMI was higher in Bhadawari than Murrah buffalo calves. Digestibility of DM, OM and CP were comparable in Bhadawari and Murrah buffalo calves. NDF and ADF digestibility were higher in Bhadawari than Murrah buffaloes though not statistically significant. DCP intake (g/d) was higher (271 vs 225) in July in both the breeds as compared to September (218 vs 197) whereas TDN intake was similar for both the periods. Daily live weight gain (g/d) was significantly higher in Murrah buffalo than Bhadawari buffalo calves. Thus it was concluded that nutrient utilization was similar under grazing with supplementation in both the breeds however, daily live weight gain was higher in Murrah when compared with Bhadawari buffalo calves.